Semantic and Pragmatic Analysis of the Future Tense in the Tragedy A Castro - Mojca Medvedšek; Blažka Müller Pograjc (Verba Hispanica, 2018)
This article aims to present the characteristics and functioning of the illocutionary acts in the tragedy A Castro by António Ferreira (1528-1569), which are marked as a series of decisions, expressed as predictions of the speaker (the protagonist, Pedro Infante) belonging to the sphere of the future. This future is known, historically proven and represents one of the most astonishing chapters of Portuguese history as well as of literary production. The study focuses on the final monologue of the Act V of the tragedy, which presents a strong dramatic potential, analysing the two sequences of the monologue and highlighting different types of illocutionary acts (Searle, 1979; Gouveia, 1996; Atienza, 2005). The authors pay special attention to the relation of the speaker towards the propositional content and the pragmatic features of the linguistic means, used to persuade the receiver that the speaker’s intentions are firm, certain, and orientated to the future, although not realized within the dramatic time of tragedy.